The effect of gluten free diet on markers of celiac disease and association with behavioral symptoms in children diagnosed with Autism Spectrum Disorders - Ghalichi, Faezeh; Ostadrahimi, Alireza; Malek, Ayyoub; Ghaemmaghami, Jamal (Progress in Nutrition, 2016)
Purpose: The objectives of this study were to measure markers of celiac disease before and after implementing a gluten free diet and also evaluating its association with autism severity. Methods: The present randomized clinical trial was accomplished over 80 subjects diagnosed with Autism Spectrum Disorders (ASD) by the Autism Diagnostic Interview-Revised (ADI-R). Participants were randomly divided into Gluten Free Diet (GFD) and regular diet groups for 6 weeks. Immunological markers consisting of IgA, tTGIgA, tTGIgG and EMAIgG were measured. Findings: In this study, 6 patients were tTGIgA positive. In the GFD group, tTGIgA decreased insignificantly (from 3.62 ± 4.25 to 3.41 ± 3.51 U/ml; P